Shoulder Injuries in Padel Players: a Systematic Review - Septiani, Miranda; Sulistyaningsih, RA Lisya Anggraeni (Dinasti Research, 2026)
Shoulder injuries are among the most common orthopedic problems in padel athletes due to the sport’s repetitive overhead movements, rapid rotations, and high mechanical load on the glenohumeral joint. This study aimed to analyze the prevalence, characteristics, and risk factors of shoulder injuries in padel players based on a systematic review of research articles published between 2022 and 2025. The method employed was a systematic review following the PRISMA 2020 guidelines. Articles were selected according to predefined inclusion and exclusion criteria. The findings indicate that upper extremity injuries, particularly shoulder injuries, show a significant incidence among padel players. The most frequently reported conditions include rotator cuff tendinopathy, shoulder impingement syndrome, and scapulohumeral biomechanical alterations. Major risk factors identified were overuse, muscle strength asymmetry, altered shoulder kinematics, and high training loads without adequate periodization. Diagnosis was commonly established through a combination of orthopedic clinical examination and imaging modalities such as MRI or ultrasound. In conclusion, shoulder injuries in padel athletes are closely associated with biomechanical factors and training load. Preventive strategies focusing on rotator cuff strengthening and scapular stabilization are recommended to reduce injury risk and optimize athletic performance.